An overview of jet-mode AGN feedback and the prospects for studying its cosmic evolution with LOFAR. Issue Volume 10:Issue S313(2014) (24th March 2015) - Bîrzan, L.; Rafferty, D. A.; Brüggen, M.; ,
Abstract: Chandra revealed cavities in the hot atmospheres of many nearby clusters. These cavities are tracers of a strong coupling between the relativistic plasma in radio sources and the cooling, thermal gas in clusters. They demonstrate clearly that the AGN affects the cooling gas that leads to star formation and galaxy growth and allow a direct measurement of the bulk of the AGN's power. Together with radio data, the cavities allow us to derive scaling relations between mechanical (cavity) and radio power that can be used to estimate the AGN feedback power when direct measurement of the cavities is not possible. We review the importance of such relations for extending current studies of feedback with new and upcoming radio telescopes such as LOFAR and SKA.